2020
DOI: 10.2147/cmar.s238132
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of RSK4 on Biological Characteristics of Gastric Cancer</p>

et al.

Abstract: Purpose: Gastric cancer is one of the most common cancers with high mortality. Emerging evidences show that ribosomal s6 kinase4 (RSK4) may be an anti-oncogene in several types of cancers, while its function in GC is still unclear. In the present study, we investigated the role of RSK4 in GC progression using MGC-803 and HGC-27 cell lines in vitro and in vivo. Methods: The expression of RSK4 in gastric cancer cells was evaluated using RT-qPCR and Western blot analysis. We transfected cells with RSK4 siRNA to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 22 publications
0
25
2
Order By: Relevance
“…Similarly, in gastric cancer, reducing the expression of RSK4 inhibits cell apoptosis, leading to enhanced cell proliferation, migration, and invasion, and promotes tumor occurrence in vivo. 1 These results indicate that RSK4 has a tumor suppressor effect in a variety of cancers. However, in lung adenocarcinoma, RSK4 is highly expressed, and is closely related to TNM stage, tumor diameter, lymph node metastasis, and distant metastasis, and is considered useful for the diagnosis of lung adenocarcinoma, as well as predicting the progression of this disease.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Similarly, in gastric cancer, reducing the expression of RSK4 inhibits cell apoptosis, leading to enhanced cell proliferation, migration, and invasion, and promotes tumor occurrence in vivo. 1 These results indicate that RSK4 has a tumor suppressor effect in a variety of cancers. However, in lung adenocarcinoma, RSK4 is highly expressed, and is closely related to TNM stage, tumor diameter, lymph node metastasis, and distant metastasis, and is considered useful for the diagnosis of lung adenocarcinoma, as well as predicting the progression of this disease.…”
Section: Discussionmentioning
confidence: 82%
“… 1 , 31 , 32 Moreover, our previous study has shown that the expression of RSK4 has an inhibitory effect on the progression of gastric cancer. 1 However, reports on miRNAs that target RSK4 in gastric cancer are limited. The present study aimed to explore the biological functions of RSK4-targeting miRNAs in gastric cancer to provide a basis for its role in tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations